KAJIAN KEBIASAAN MAKANAN, LUAS RELUNG, DAN INTERAKSI ANTAR JENIS IKAN DI WADUK CIRATA, JAWA BARAT [Study on food habit, niche breadth, and species interaction of food in Cirata Reservoir, West Java] - Didik Wahju Hendro Tjahjo; Sri Endah Purnamaningtyas (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2008)
Development of fish culture in float net cages in Cirata Reservoir was very fast so overstep the amount that permitted. The activities had impacted at growth of fish community. Those resulted of exploiting of food resources potency available was not yet ever been optimal. Therefore, purpose of this research was evaluated to role and fish species interaction in exploiting of food resource in Cirata Reservoir. The study was conducted in Ir. H. Djuanda Reservoir on March, June, and December 2007. Those observations were conducted with stratified method. Fish species were caught during this studies e.g. nilem(Psteochilus hasselti), patin (Pangasionodon hypopthalmus), nila (Oreochromis niloticus), benteur (Puntius binotatus), hanipal Hampala macrolepidota), oscar (Amphilophus citrinellus), kebogerang (Mystus Negriceps), goldsom (Amphilophus alfari), lalawak Barbonymus bramoides), tagih (Mystus nemurus), marinir (Parachromis managuense), betutu (Oxyeleotris marmorata), mas (Cyprinus carpio), bawal (Colossoma macropopomum) and gabus (Channa striata). Nila has food niche breadth the widest ness, this mean that the fish had much more adaptation ability of food fluctuation compared to the other fish species herbivore. Food competition opportunity between fish species in Cirata Reservoir was be very low. The condition could be interpreted that structure role of the fish community relative stabilize, because food resource was very copious availableness and had not yet been exploited in an optimal fashion. Therefore, the effort was improve exploiting of the food resource could be done by the stocking of herbivore fish, especially plankton feeder.",